(untitled) (Journal of Pharma Insights and Research, 2025)
A simple, sensitive, and precise reverse-phase high-performance liquid chromatography (RP-HPLC) method was developed and validated for the quantitative determination of Celecoxib in pharmaceutical capsule formulations. Chromatographic separation was achieved on a Develosil ODS HG (250×4 mm, 10μm) column using a mobile phase consisting of acetonitrile:water (60:40 v/v) with 1mL triethylamine and 1mL orthophosphoric acid at a flow rate of 1.0 mL/min. UV detection was performed at 265 nm. The method demonstrated excellent linearity (r² > 0.999) over the concentration range of 50-150% of the test concentration. The precision of the method was confirmed with RSD values below 2.0%. Accuracy studies showed mean recovery values between 98.8-99.7% across all concentration levels. Forced degradation studies under various stress conditions (acid, base, oxidation, thermal, humidity, and photolytic) confirmed the stability-indicating nature of the method. The developed method successfully separated Celecoxib from its degradation products and known impurities. Solution stability studies indicated that standard and sample solutions remained stable for 6 days when stored at 2-8°C and 1 day at room temperature. The method was validated according to ICH guidelines for specificity, linearity, accuracy, precision, range, and robustness. The validated method proved suitable for routine quality control analysis and stability studies of Celecoxib capsule formulations